Green synthesis of Ag/Fe3O4 nanoparticles using Mentha longifolia flower extract: evaluation of its antioxidant and anti-lung cancer effects. Issue 12 (December 2022) - Wang, Lei; Karmakar, Bikash; Al-Saeed, Fatimah A.; ٍShati, Ali A.; Bani-Fwaz, Mutasem Z.; El-kott, Attalla F.
Abstract: Herein, a bio-inspired synthetic method for Ag NP adorned biofunctionalized magnetic nanocomposite has been demonstrated. In the procedure, Mentha longifolia flower extract was employed as a template for the green reduction of immobilized Ag ions to corresponding NPs and subsequent stabilization. The phytochemical modification also facilitated the Fe3 O4 NPs to protect from self-aggregation. The as-synthesized Ag/Fe3 O4 nanocomposite material was characterized by SEM, TEM, EDX, elemental mapping, VSM, XRD and ICP-OES methods. Towards the biological application, the material was first explored in the anti-oxidant study following DPPH assay and it exhibited a significant radical scavenging capacity. The application of Ag/Fe3 O4 nanocomposite was further progressed in the anticancer study against standard human lung cancer cell lines (A549 and H358). Cytotoxicity of the material against the cell lines were determined in terms of % cell viability following MTT method and was found to decrease with increase in the material load. Abstract : Ag nanoparticles; Magnetic nanocomposite; Green synthesis; Lug cancer.